Efficacy of buffered acetylsalicylic acid and enteric-coated acetylsalicylic acid on platelet aggregation in patients with chronic coronary syndrome and type 2 diabetes (CASCADE): single-center observational comparative study - Zh. D. Kobalava; A. S. Pisaryuk; A. A. Filkova; E. S. Tukhsanboev; A. N. Amirova; A. D. Korneichuk; G. S. Pavlikov; L. R. Burkhanova; I. A. Meray; M. A. Panteleev; A. N. Sveshnikova (Российский кардиологический журнал, 2025)
Background. There is a lack of data on the incidence of aspirin nonresponsiveness and the efficacy of different forms of ASA in patients with diabetes.Aim. To evaluate the efficacy of buffered versus enteric-coated ASA based on the frequency of high residual platelet reactivity (HRPR) as measured by the VerifyNow Aspirin Test in patients with chronic coronary syndrome (CCS) and type 2 diabetes (T2D).Material and methods. The single-center observational parallel-group comparative study (CASCADE) included patients over 18 years of age with CCS and T2D who were prescribed a buffered form of ASA (Cardiomagnyl 75 mg/day) or an entericcoated form of ASA (Thrombo ACC® 100 mg/day or Aspirin® Cardio 100 mg/day) in routine practice prior to inclusion in the study and were randomly selected from the general consultative and diagnostic department of the hospital. According to the routine prescribed therapy, patients were divided into 2 following groups: patients taking Cardiomagnyl 75 mg/day; patients taking Thrombo ACC® 100 mg/day or Aspirin® Cardio 100 mg/day. At the first visit patients signed informed consent and received a card to assess the compliance of ASA intake, while at the second visit (after 7 days with 100% compliance) patients underwent laboratory assessment of ASA efficacy by VerifyNow Aspirin Test and light transmission aggregometry according to a special protocol including arachidonic acid induction. And the third visit included a call to the patient after 90 days, according to which information was collected about all events that occurred with the patient since the signing of the informed consent. The primary endpoint of the study was the incidence of HRPR on the background of ASA administration according to the VerifyNow Aspirin Test. The primary endpoint, tolerability and safety were evaluated in all patients included in the study. This study was registered at ClinicalTrials.gov, NCT06716255, and is currently completed.Results. Between February 28, 2024, and May 17, 2024, 200 patients were screened and 84 were successfully enrolled in the study, of which 42 patients received the enteric-coated ASA (Thrombo ACC® 100 mg/day, n=21; Aspirin® Cardio 100 mg/day, n=21) and 42 patients received the buffered ASA absorbed in the stomach (Cardiomagnyl 75 mg/day). The mean age of the study subjects was 68,9 years (standard deviation ±10,2); 34 (40,5%) patients were female and 50 (59,5%) were male. The study was terminated early because of larger than expected intergroup differences. At the time of the interim analysis (May 17, 2024), the incidence of HRPR according to the VerifyNow Aspirin Test was higher in the group of patients receiving the enteric-coated ASA (10 (23,8%) vs 3 (7,1%), p=0,035). By day 90, the incidence of composite endpoint (all-cause mortality; hospitalization for any cause; any ischemic (thrombotic) events) in the buffer ASA group was 7,1% (n=3), which was lower than in the enteric-coated ASA group, which was 16,7% (n=7), mainly due to hospitalisations. However, there were significant associations (p=0,178). One ischemic event was recorded in the enteric-coated ASA group, and there were no ischemic events in the buffered ASA group (p=0,314). There were no fatal outcomes in both groups during the follow-up period. At the same time, the rate of haemorrhagic events in patients with CCS and T2D while taking buffered and enteric-coated ASA was 3 (7,1%) and 4 (9,5%), respectively (p=0,693).Conclusion. Administration of a buffered form of ASA absorbed in the stomach in a group of patients with T2D could potentially allow for a reduction in the number of ASA nonresponsiveness, which could further lead to a reduction in the number of significant clinical events without loss of safety.